Sexual and reproductive health considerations in the care of young adults with inflammatory bowel disease: A multidisciplinary conversation - Sydney Reed; Amy K. Bugwadia; Sneha Dave; Hannah E. Wilson; Prathikka Ramesh; Hilary K. Michel (Health Care Transitions)
The effects of inflammatory bowel disease (IBD) and the medications used to treat it on sexual and reproductive health can be significant, impacting the quality of life of patients across gender identities. This article presents insights from a roundtable discussion facilitated by the Crohn's and Colitis Young Adults Network (CCYAN) between young adult patients with IBD and medical professionals, including physicians, nurses, psychologists, and trainees/medical students. It underscores the distinction between sexual and reproductive health, emphasizing the need to address both aspects comprehensively. The discussion identified key themes, including sexual dysfunction and well-being in IBD patients; discussing sexual health with young adult IBD patients; current research in reproductive health: gaps and opportunities; discussing reproductive health with young adult IBD patients; and providing resources and comprehensive multidisciplinary care.